Anion photoelectron spectroscopy and quantum chemical calculations of bimetallic niobium–aluminum clusters NbAln−/0 (n = 3–12): identification of a half-encapsulated symmetric structure for NbAl12−. Issue 8 (14th February 2023) - Yan, Shuai-Ting; Long, Zhen-Chao; Xu, Xi-Ling; Xu, Hong-Guang; Zheng, Wei-Jun
Abstract : NbAl12 − has a C 3v symmetric half-encapsulated structure, which can be viewed as a NbAl6 regular hexagon over a bowl-shaped Al6 structure. Abstract : Bimetallic niobium-doped aluminum clusters, NbAl n −/0 ( n = 3–12), are investigated through a synergetic combination of size-selected anion photoelectron spectroscopy and theoretical calculations. It is found that the dominant structures of NbAl n − anions with n = 3–8 can be described by gradually adding Al atoms to the NbAl3 − core. Starting from n = 9, the lowest-energy geometric structures of NbAl9–12 − transform into bilayer structures. In particular, NbAl12 − has a C 3v symmetric structure, which can be viewed as a NbAl6 regular hexagon over a bowl-shaped Al6 structure. More detailed analyses indicate that NbAl9 and NbAl12 − possess unusual stability, which may be attributed to their closed-shell electron configurations with superatomic features.